The Impact of Remuneration and Work Climate on Outsourced Workers’ Motivation at PT XYZ West Java - Achmad, Setiyo Budi (Electronic Journal of Education, Social Economics and Technology, 2025)
Outsourced workers play a vital role in supporting company operations, yet they often face motivational challenges due to limited rights, recognition, and job security. This study aims to examine the influence of remuneration and work climate on the work motivation of outsourced personnel specifically housekeeping, security, and drivers at PT XYZ, West Java Regional Office. Employing a descriptive quantitative method with an associative approach, the research involved 115 purposively selected respondents. Data were analyzed using multiple linear regression with SPSS version 25. The results reveal that both remuneration and work climate have a positive and significant impact on work motivation, both individually and jointly. The coefficient of determination (R²) of 86.5% indicates that these two variables substantially explain the variance in motivation levels. Remuneration serves as an extrinsic driver, enhancing enthusiasm through perceptions of financial fairness, while work climate acts as an intrinsic factor, fostering psychological comfort and organizational attachment. In conclusion, improving outsourced workers’ motivation requires not only fair compensation but also the cultivation of a supportive and human-centered work environment. These findings carry important implications for the formulation of equitable and sustainable human resource policies, particularly in managing outsourced labor within corporate structures.